Pengelolaan Pelayanan Guest Service Attendant Pada Masa Pandemi Covid-19 Di Hotel The Ritz Carlton - Pianti Yudira Dewi; I Wayan Seniartha (Journal of Hospitality Accommodation Management (JHAM), 2023)
This study was conducted to find out how to manage Guest Service Attendant services during the covid-19 pandemic. This study uses data collection techniques by conducting interviews and documentation related to the research topic. The data analysis technique used is descriptive qualitative by describing the results of interviews from the Guest Service Supervisor at The Ritz Carlton Hotel Bali. Based on the results of the interview analysis, the management of the Guest Service Attendant at The Ritz Carlton Bali Hotel still needs to be improved. This can be seen from the 4 basic principles of management that there are only 2 points that are carried out maximally while the 2 points are less than optimal and need to be improved again. For this reason, it is expected that the Guest Service Supervisor can further improve teamwork in working so that all basic principles in management can be carried out to the maximum.